Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1097/01.aids.0000341775.94123.75
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability of women in southern Africa to infection with HIV: biological determinants and priority health sector interventions

Abstract: Priority health sector interventions for preventing HIV are: male and female condom programming; prevention and control of STI; outreach to most vulnerable populations; HIV testing in all patient-provider encounters; male circumcision; and the integration of HIV prevention within sexual and reproductive health services. Future interventions during acute HIV infection and microbicides will reduce women's biological vulnerability. Far-reaching measures, such as sexual equity and alcohol control, create condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
73
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(77 citation statements)
references
References 137 publications
4
73
0
Order By: Relevance
“…Gender differences in survival may also result from differences in the uptake or adherence to antiretroviral therapy (ART). Women's greater susceptibility is attributed to a number of biological mechanisms, including differences in genital immunology that are well described in the literature (Chersich and Rees 2008;Higgins, Hoffman, and Dworkin 2010;Yi et al 2013). A variety of co-factors may alter susceptibility to HIV infection, including the presence of both viral and bacterial sexually transmitted infections (STI) (Cohen 2004;Glynn et al 2001;Hertog 2008;UNAIDS/WHO 2000) 8 and male circumcision (Auvert et al 2005;Hertog 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gender differences in survival may also result from differences in the uptake or adherence to antiretroviral therapy (ART). Women's greater susceptibility is attributed to a number of biological mechanisms, including differences in genital immunology that are well described in the literature (Chersich and Rees 2008;Higgins, Hoffman, and Dworkin 2010;Yi et al 2013). A variety of co-factors may alter susceptibility to HIV infection, including the presence of both viral and bacterial sexually transmitted infections (STI) (Cohen 2004;Glynn et al 2001;Hertog 2008;UNAIDS/WHO 2000) 8 and male circumcision (Auvert et al 2005;Hertog 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The contributions of pregnancy Marston et al 2013;Morrison et al 2007) and hormonal contraceptives to women's disproportionally high infection rates are less certain (WHO 2012). Other factors with repercussions for HIV transmission pertain to the sex act itself, including vaginal versus anal sex, the use of vaginal drying agents, and forced sex (Chersich and Rees 2008). Finally, gender differences in ART uptake might alter the gender ratio of infections because onward transmission is reduced due to viral suppression.…”
Section: Introductionmentioning
confidence: 99%
“…[34][35][36][37] Earlier studies showed that pregnant women are at a higher risk of HIV infection than lactating or other women, possibly due to physiological changes that a woman undergoes during pregnancy. 38 High levels of oestrogen and progesterone either during pregnancy or from exogenous sources could cause changes in the structure of the genital mucosa or cause immunological changes, such as an increase in mucosal lymphoid aggregates or hormone-induced over expression of co-receptors associated with HIV infection. Supporting evidence suggests that women have a window of vulnerability approximately seven to ten days after ovulation during their menstrual cycle in which the potential for viral infectivity in the female reproductive tract is increased.…”
Section: Discussionmentioning
confidence: 99%
“…There are many advantages gained from incorporation of STI control into HIV program or rather from providing a major integrated approach preventive interventions for reproductive and sexually transmitted infections of which HIV is just one [26,27].…”
Section: Concurrent Stis and Hiv Acquisitionmentioning
confidence: 99%